Transparent two-phase glass ceramic for rare earth induction associated crystallization, preparation method and application

By controlling the precipitation of functional crystals in the glass and using them as the crystal nucleus to precipitate another crystal, a transparent biphasic microcrystalline glass with rare earth-induced correlation crystallization was prepared, which solved the inability to crystal distribution in traditional biphasic microcrystalline glasses. The problem of control significantly improves the luminous efficiency.

CN119461859APending Publication Date: 2025-02-18LUOYANG NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411620780.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In existing biphasic microcrystalline glasses, the distribution of crystals in the glass is uncontrollable, resulting in low luminescence efficiency and uneven crystal precipitation after heat treatment, affecting optical performance.

Method used

By controlling the precipitation of one functional crystal in the glass and using it as the crystal nucleus to separate another functional crystal, a transparent biphasic microcrystalline glass with rare earth-induced correlation crystallization was prepared.

Benefits of technology

The controllability of crystal distribution is achieved, the energy transfer between rare earths and transition metal ions is enhanced, and the luminescence efficiency is significantly improved, especially the ultra-wideband luminescence intensity of transition metal ions is increased by more than 100 times.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461859A_ABST
    Figure CN119461859A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of optical functional materials, in particular to transparent biphase glass ceramics for rare earth induction associated crystallization, a preparation method and application. According to the preparation method, SiO2, ZnF2 and KF are taken as matrix glass raw materials, rare earth and transition metal ions are taken as optical activity doping ions, precursor glass is prepared through melting, and the transparent biphase glass ceramic is obtained through annealing, heat treatment and associated devitrification. The transparent dual-phase glass ceramic prepared by the invention contains KYb3F10 nanocrystals and KZnF3 nanocrystals, and compared with glass ceramic containing K2SiF6 and ZnF2 nanocrystals, the bandwidth luminous efficiency of the transparent dual-phase glass ceramic is improved by more than 100 times; the method provides good reference for preparation of two-phase glass ceramics of more different systems, and has important application prospects in the fields of broadband optical fiber amplifiers and tunable optical fiber lasers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of optical functional materials, and in particular to a transparent dual-phase glass-ceramic with rare earth induced correlated crystallization, a preparation method and an application thereof. Background Art

[0002] Glass-ceramics is a type of composite solid functional material containing several glass phases and crystal phases, which is obtained by controlling the crystallization process of glass through appropriate heat treatment process. Glass-ceramics can provide a stable protective environment, a strong crystal field and a low phonon energy luminescence environment for luminescent ions, and has great application value in many fields such as high-efficiency lasers, 3D information storage, LED lighting and display, etc.

[0003] As the degree of social informatization continues to deepen, people's demand for high-performance, multi-band luminescent optical materials is increasing day by day, and dual-phase microcrystalline glass materials have therefore received extensive attention and research. This type of material is a uniform precipitation of two different types of crystals in the glass (such as oxide (Ga2O3) and fluoride (YF3) crystals, precious metal (Au) and fluoride (NaYF4) nanocrystals, etc.), which have the excellent structural characteristics of the two crystals and can provide suitable lattice sites for different luminescent ions (such as transition metals and rare earth ions) respectively, allowing the luminescent ions to enter the crystal environment. By adjusting the distribution of crystals in the glass and regulating the energy transfer between luminescent ions, high-efficiency fluorescence emission, multi-color visible luminescence, and ultra-wideband near-infrared luminescence can be achieved.

[0004] In the past few decades, some progress has been made in the research of dual-phase glass-ceramics, but there are still some problems that need to be solved, mainly in the following two aspects: 1. Different crystals have different precipitation temperatures in glass. After heat treatment, one type of crystal often has not yet precipitated, while another type of crystal precipitates in large quantities, causing the glass-ceramic to lose transparency and seriously affecting its optical properties. Second, the distribution of the two-phase crystals in the glass is random, the distribution of the two crystals is uncontrollable, the energy transfer process between different ions is uncontrollable, and the luminescence enhancement is small.

[0005] The existence of the above-mentioned problems in dual-phase glass-ceramics has seriously hindered the practical application of dual-phase glass-ceramics in optical devices. Summary of the invention

[0006] The purpose of the present invention is to solve the shortcomings and deficiencies in the prior art and to provide a rare earth induced correlated crystallization transparent two-phase glass-ceramics and a corresponding preparation method thereof.

[0007] Regarding this preparation method, first, a functional crystal is controllably precipitated in the glass, and then using this as a crystal nucleus, another functional crystal is controllably precipitated around the crystal nucleus to obtain a dual-phase microcrystalline glass. In this way, the precipitation of the two crystals in the microcrystalline glass is related, and the distribution of the crystals is controllable, thereby solving the problem of uncontrollable crystal distribution in traditional dual-phase microcrystalline glass. When two different luminescent ions enter the dual-phase crystal respectively, the distance between the ions is extremely small, and the interaction between the ions is enhanced, thereby greatly enhancing the luminous efficiency. The present invention provides a new way to prepare high-quality dual-phase microcrystalline glass with controllable crystal distribution, and provides excellent gain materials for realizing high-efficiency solid-state lasers, multi-color LEDs, and broadband amplifiers.

[0008] The technical solution adopted by the present invention to solve its technical problem is: A method for preparing a transparent dual-phase glass-ceramic with rare earth induced correlated crystallization, the specific steps comprising: Firstly, SiO2, ZnF2, KF are used as glass matrix and rare earth ions and transition metal ions are doped as luminescent centers, and precursor glass is obtained by melting. Then, the precursor glass is subjected to a heat treatment process to undergo associated crystallization to obtain a transparent two-phase glass-ceramics.

[0009] Furthermore, the chemical composition of the glass matrix in terms of molar percentage is: (55-68)mol%SiO2-(16-22.5)mol%ZnF2-(16-22.5)mol%KF.

[0010] Furthermore, the molar percentage of the rare earth ions used in the glass matrix is ​​0.35-1.5 mol%.

[0011] Furthermore, the rare earth ion is Yb 3+ , Er 3+ , Pr 3+ 、Tm 3+ 、Nd 3+ , Tb 3+ One or more of .

[0012] Furthermore, the amount of the transition metal ion used in the glass matrix is ​​0.1-1.0 mol%, and the transition metal ion is Ni 2+ , Mn 2+ , Mn 3+ Cr 3+ , Cu + 、Co 2+ One or more of .

[0013] Furthermore, the preparation of the precursor glass is specifically as follows: First, the raw materials SiO2, ZnF2, KF, rare earth ions and transition metal ions constituting the glass matrix are mixed and ball-milled according to the proportions; The ball-milled mixed raw materials are then melted in the air at a melting temperature of 1450-1550°C for 30-60 minutes. The temperature is then lowered by 50-55°C, the molten glass is poured onto a copper plate and pressed with another copper plate to form a precursor glass.

[0014] Furthermore, the preparation of the associated crystallization is specifically as follows: First, the prepared precursor glass is annealed at 300-400°C for 2-6h; Then, the annealed precursor glass is heat treated at 500-540° C. for 3-10 hours.

[0015] A transparent two-phase microcrystalline glass with rare earth induced correlated crystallization prepared by the preparation method.

[0016] The invention discloses an application of a transparent dual-phase microcrystalline glass with rare earth induced correlated crystallization in the preparation of a broadband optical fiber amplifier or a tunable optical fiber laser.

[0017] Compared with the prior art, the present invention has the following beneficial effects: (1) When the dual-phase glass-ceramics is prepared by the method of the present invention, the crystallization temperatures of the two crystals are close, and when two appropriate amounts of crystals are formed in the glass matrix, a high optical transmittance can still be maintained; (2) The dual-phase microcrystalline glass prepared by the present invention is crystallized by rare earth induced correlation. KZnF3 crystals are KYb3F 10 Due to the crystal nucleation, the distance between crystals is very short, which can realize efficient energy transfer between rare earth and transition metal ions, thereby increasing the ultra-wideband luminescence intensity of transition metal ions by more than 100 times; (3) When the dual-phase glass-ceramics is prepared by the method of the present invention, KYb3F can be precipitated in the glass by a single heat treatment. 10 and KZnF3 crystals, the preparation process is simple, and optical fibers can be drawn and large-sized optical devices can be prepared; (4) The present invention proposes a new method for preparing dual-phase transparent glass-ceramics, which broadens the preparation methods of glass-ceramics and provides a good reference for the preparation of more different types of glass-ceramics. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 These are the X-ray diffraction patterns of Comparative Example 1, Comparative Example 2, and Example 1.

[0019] Figure 2 This is the transmission electron microscope image of Example 1.

[0020] Figure 3 It is the transmission spectra of Comparative Example 1, Comparative Example 2 and Example 1 in the 200-1100nm band, and the inset is the photo of the corresponding microcrystalline glass.

[0021] Figure 4 The microcrystalline glass prepared in Comparative Example 1, Comparative Example 2 and Example 1 was Ni 2+ Broadband near-infrared fluorescence emission spectroscopy. DETAILED DESCRIPTION

[0022] In order to enable those skilled in the art to better understand the solution of the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0023] The present invention provides a method for preparing a transparent dual-phase glass-ceramics with rare earth induced correlated crystallization, the specific steps comprising: Step (1): Preparation of precursor glass: SiO2, ZnF2, KF are used as glass matrix and rare earth ions and transition metal ions are doped as luminescent centers, and the precursor glass is obtained by melting. Specifically: First, the raw materials SiO2, ZnF2, KF, rare earth ions and transition metal ions constituting the glass matrix are mixed and ball-milled according to the proportions; Then, the ball-milled mixed raw materials are melted in air at a melting temperature of 1450-1550°C for 30-60 minutes; then, the temperature is lowered by 50-55°C, the molten glass is poured onto a copper plate and pressed with another copper plate to form a precursor glass; The chemical composition of the glass matrix in terms of molar percentage is: (55-68) mol% SiO2-(16-22.5) mol% ZnF2-(16-22.5) mol% KF; The molar percentage of rare earth ions in the glass matrix is ​​0.35-1.5 mol%. The rare earth ions are Yb 3+ , Er 3 + , Pr 3+ 、Tm 3+ 、Nd 3+ , Tb 3+ One or more of; The amount of transition metal ions used in the glass matrix is ​​0.1-1.0 mol%, and the transition metal ions are Ni 2+, Mn 2+ , Mn 3+ Cr 3+ , Cu + 、Co 2+ One or more of .

[0024] Step (2): Correlated crystallization, the precursor glass is subjected to a heat treatment process to correlate crystallize to obtain a transparent two-phase microcrystalline glass. Specifically: First, the prepared precursor glass is annealed at 300-400°C for 2-6h; Then, the annealed precursor glass is heat treated at 500-540° C. for 3-10 hours.

[0025] The following is a comparison between the dual-phase glass-ceramics prepared by the preparation method of the present invention and the single-phase glass-ceramics and conventional dual-phase glass-ceramics, and the corresponding results are analyzed.

[0026] Embodiment 1: A kind of KYb3F 10 , transparent dual-phase glass-ceramics of KZnF3 crystals, The fluoride oxide glass matrix is ​​composed of SiO2, ZnF2, and KF, and the amounts of each of them are 60 mol.%, 20 mol.%, and 20 mol.%, respectively, totaling 100 mol.%; NiO is used as the source of externally doped transition metal ions, with the doping amount being 0.2 mol.%; YbF3 is used as the source of external rare earth ions, and the doping amount is 1.0 mol.%.

[0027] First, the glass matrix, transition metal ions and rare earth ion raw materials are mixed according to the proportion and stirred for 30 minutes using a ball mill to ensure that the drugs can be evenly mixed; Transfer the mixed raw materials into a platinum crucible, place the platinum crucible in a high-temperature furnace at 1450°C, cover it with a quartz lid, and melt for 30 minutes. After the melting is completed, lower the temperature to 1400°C; The glass liquid is poured onto a copper plate and pressed with another copper plate to obtain a precursor glass.

[0028] The precursor glass was annealed in a muffle furnace at 400°C for 3 hours to eliminate the internal stress in the glass. The annealed precursor glass was placed in a precision annealing furnace and annealed at 540°C for 10 hours to obtain KYb3F 10 , dual-phase transparent microcrystalline glass of KZnF3 crystals.

[0029] Comparative Example 1: A single-phase glass-ceramic containing K2SiF6 crystals, In this comparative example, the fluoride oxide glass matrix is ​​composed of SiO2, ZnF2, and KF, and their respective amounts are 60 mol.%, 20 mol.%, and 20 mol.%, respectively, totaling 100 mol.%.

[0030] NiO was used as an externally doped transition metal ion, with the doping amount being 0.2 mol%.

[0031] The specific preparation method is: Weigh SiO2, ZnF2 and KF chemicals according to the calculated ratio respectively; Put all the above raw materials in an agate jar and stir them in a ball mill for 30 minutes to make the medicines evenly mixed; Transfer the mixed raw materials into a platinum crucible, place the platinum crucible in a high-temperature furnace at 1450°C, cover it with a quartz lid, and melt for 30 minutes. After the melting is completed, lower the temperature to 1400°C; The glass liquid is poured onto a copper plate and pressed with another copper plate to obtain a precursor glass.

[0032] The precursor glass was annealed in a muffle furnace at 400°C for 3 hours to eliminate the internal stress in the glass. The annealed precursor glass was placed in a precision annealing furnace and annealed at 540°C for 3 hours to obtain a single-phase microcrystalline glass containing K2SiF6 crystals.

[0033] Comparative Example 2: A dual-phase glass-ceramic containing K2SiF6 and ZnF2 crystals. Using the same basic glass composition as in Comparative Example 1, the doping of transition metal ions remains the same, and the specific preparation method of the precursor glass also remains the same; The heat treatment conditions were changed to 540°C for 10 h to obtain a dual-phase glass-ceramics containing K2SiF6 and ZnF2 crystals.

[0034] Figure 1 The X-ray diffraction patterns of the glass products prepared in Comparative Example 1, Comparative Example 2 and Example 1 are shown in FIG. Figure 1 It can be seen that when Ni 2+ When the single-doped precursor glass was heat treated for 3 hours, K2SiF6 crystals were precipitated in the glass of Comparative Example 1, and when the heat treatment was performed for 10 hours, ZnF2 crystals were precipitated in the glass of Comparative Example 2. 3+ After heat treatment for 10 h, KYb3F was precipitated in Example 1. 10 , KZnF3 two-phase crystal. Among them, KYb3F 10 So Yb 3+ The crystal nucleus is precipitated in situ, while the KZnF3 crystal is KYb3F 10 Position nucleus associated precipitation.

[0035] Figure 2 It is the transmission electron microscope picture of Example 1. Figure 2 It can be seen that KZnF3 is next to KYb3F 10 The crystal distribution further confirmed that KZnF3 crystals are mainly composed of KYb3F 10 It is a crystal nucleus-related precipitation. 3+ and Ni 2+ Both have entered the crystal, and the distance between them is very short, which can achieve efficient energy transfer.

[0036] Figure 3 The transmittance spectra of Comparative Example 1, Comparative Example 2 and Example 1 in the 200-1100 nm band are shown. It can be seen from the figure that Comparative Example 1 and Example 1 can still maintain relatively high transmittance, while the transmittance of Comparative Example 2 drops extremely rapidly.

[0037] Figure 4 The microcrystalline glass prepared in Comparative Example 1, Comparative Example 2 and Example 1 was Ni 2+ Broadband near-infrared fluorescence emission spectrum. From the results, it can be seen that due to the low phonon energy of KZnF3 crystal and Yb 3+ To you 2+ The reason for efficient energy transfer is that Ni 2+ The near-infrared emission intensity is increased by more than 100 times compared with Comparative Examples 1 and 2.

[0038] Through the above experiments, it can be proved that the dual-phase glass-ceramics prepared by the preparation method provided by the present invention can The crystallization temperatures of the two crystals are close. When two appropriate amounts of crystals are formed in the glass matrix, high optical transmittance can still be maintained. The dual-phase microcrystalline glass prepared by the present invention is crystallized by rare earth-induced correlation. KZnF3 crystals are KYb3F 10 Due to the crystal nucleus precipitation, the distance between crystals is very short, which can realize efficient energy transfer between rare earth and transition metal ions, thereby increasing the ultra-wideband luminescence intensity of transition metal ions by more than 100 times.

[0039] The preparation method of the present invention can precipitate KZnF3 crystals and KYb3F in glass through a single heat treatment. 10 Crystals have a simple preparation process and can be used to draw optical fibers and prepare large-sized optical devices.

[0040] It is obvious to those skilled in the art that the above embodiments are not intended to be exhaustive or limit the embodiments to the specific precise forms disclosed. It is obvious to those skilled in the art that certain modifications, combinations and variations can be made based on the above teachings.

Claims

1. A method for preparing a transparent dual-phase glass-ceramics with rare earth induced correlated crystallization, characterized in that: The specific steps include: Firstly, SiO2, ZnF2, KF are used as glass matrix and rare earth ions and transition metal ions are doped as luminescent centers, and precursor glass is obtained by melting. Then, the precursor glass is subjected to a heat treatment process to undergo associated crystallization to obtain a transparent two-phase glass-ceramics.

2. The preparation method according to claim 1, characterized in that: The chemical composition of the glass matrix in terms of molar percentage is: (55-68)mol%SiO2-(16-22.5)mol%ZnF2-(16-22.5)mol%KF.

3. The preparation method according to claim 1 or 2, characterized in that: The molar percentage of the rare earth ions used in the glass matrix is ​​0.35-1.5 mol%.

4. The preparation method according to claim 3, characterized in that: The rare earth ion is Yb 3+ , Er 3+ , Pr 3+ 、Tm 3+ 、Nd 3+ , Tb 3+ One or more of .

5. The preparation method according to claim 1 or 2, characterized in that: The amount of the transition metal ion used in the glass matrix is ​​0.1-1.0 mol%, and the transition metal ion is Ni 2+ , Mn 2+ , Mn 3+ Cr 3+ , Cu + 、Co 2+ One or more of .

6. The preparation method according to claim 1, characterized in that: The preparation of the precursor glass is specifically as follows: First, the raw materials SiO2, ZnF2, KF, rare earth ions and transition metal ions constituting the glass matrix are mixed and ball-milled according to the proportions; The ball-milled mixed raw materials are then melted in the air at a melting temperature of 1450-1550°C for 30-60 minutes. The temperature is then lowered by 50-55°C, the molten glass is poured onto a copper plate and pressed with another copper plate to form a precursor glass.

7. The preparation method according to claim 1, characterized in that: The preparation of the associated crystallization is specifically as follows: First, the prepared precursor glass is annealed at 300-400°C for 2-6h; Then, the annealed precursor glass is heat treated at 500-540° C. for 3-10 hours.

8. A transparent two-phase glass-ceramic with rare earth induced correlated crystallization prepared by the preparation method according to any one of claims 1 to 7.

9. Use of a transparent dual-phase glass-ceramic with rare earth induced correlated crystallization prepared by the preparation method according to any one of claims 1 to 7 in the preparation of a broadband fiber amplifier or a tunable fiber laser.